2022
DOI: 10.1186/s12931-022-02151-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of COVID-19 patients at risk of hospital admission and mortality: a European multicentre retrospective analysis of mid-regional pro-adrenomedullin

Abstract: Background Mid-Regional pro-Adrenomedullin (MR-proADM) is an inflammatory biomarker that improves the prognostic assessment of patients with sepsis, septic shock and organ failure. Previous studies of MR-proADM have primarily focussed on bacterial infections. A limited number of small and monocentric studies have examined MR-proADM as a prognostic factor in patients infected with SARS-CoV-2, however there is need for multicenter validation. An evaluation of its utility in predicting need for ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 42 publications
(66 reference statements)
2
16
0
Order By: Relevance
“…Higher endothelial damage biomarkers (ProADM and proendothelin) showed greater predictive mortality value compared to C-reactive protein, procalcitonin, and Ddimer [26,49]. Elevated levels of proADM (>1.76 nmol/L) or proendothelin (>75 nmol/L) were associated with a higher rate of ICU admission, in-hospital mortality, and shorter time to death [26], as seen in other series of cases [50,51]. Notably, initial levels of CitH3, cfDNA, and sP-selectin were not associated with higher mortality.…”
Section: Discussionsupporting
confidence: 59%
“…Higher endothelial damage biomarkers (ProADM and proendothelin) showed greater predictive mortality value compared to C-reactive protein, procalcitonin, and Ddimer [26,49]. Elevated levels of proADM (>1.76 nmol/L) or proendothelin (>75 nmol/L) were associated with a higher rate of ICU admission, in-hospital mortality, and shorter time to death [26], as seen in other series of cases [50,51]. Notably, initial levels of CitH3, cfDNA, and sP-selectin were not associated with higher mortality.…”
Section: Discussionsupporting
confidence: 59%
“…In one study, MR-proADM levels on hospital admission showed excellent predictive value for 28-day mortality in COVID-19 patients with an AUC of 0.91 and were also highly predictive of progression to severe disease 21 . Other studies on MR-proADM have also shown good prediction with an area under the curve of approximately 0.80 [22][23][24] , which suggests that bio-ADM has an important pathophysiological role in COVID-19.…”
Section: Adrenomedullin and Critical Covid-19mentioning
confidence: 79%
“…Recently, several studies have shown a relationship between high levels of adrenomedullin and severity of illness in hospitalized COVID-19 patients [21][22][23][24][25][26] . Adrecizumab has been tested to treat severe COVID-19 ARDS in a small uncontrolled case series 27 .…”
Section: Adrenomedullin and Critical Covid-19mentioning
confidence: 99%
See 2 more Smart Citations